Pengaruh antara Iklim Organisasi dan Kepuasan Kerja dengan Organizatioanal Citizenship Behaviour Pada Guru MIN Se Kota Pekanbaru - N. Nurhasnawati; Mhd. Subhan (Indonesian Journal of Islamic Educational Management, 2018)
This research aimed at investigating the influence of organizational climate and job satisfaction on organizational citizenship behavior of Islamic elementary school teachers in Pekanbaru. The population of this research was teachers of Islamic elementary schools in Pekanbaru. The sampling technique of this research was simple random sampling which consisted of 164 samples. This research used two instruments: organizational climate and job satisfaction instruments, and organizational citizenship behavior. The validity of data was conducted with 3 experts which consisted of one expert of primary education and 2 experts of educational management. The reliability of 3 instruments was organization climate with Cronbach Alpha 0.84, job satisfaction with Cronbach Alpha 0.77, and organizational citizenship behavior with Cronbach Alpha 0.81. The analysis of data used SPSS Software Version 22.0. The research findings demonstrated that the descriptive level of job satisfaction toward organizational citizenship behavior was intermediate. However, it was significantly difference from climate organization. In addition, the inferential analysis with multiple regression about the influence of organizational climate and job satisfaction on organizational citizenship was 80.8%. It means that other factors was 19.2%. Therefore, the principal required to establish a program to improve the influence the organizational climate and job satisfaction on organizational citizenship behavior of Islamic elementary school teachers in Pekanbaru.